Zeolite Imidazolate Framework-Based Platform for the Electrochemical Detection of Epinephrine - Soosaimanickam, Charlin; Sakthivel, Arunkumar; Murugavel, Kathiresan; Alwarappan, Subbiah (Journal of the Electrochemical Society, 2023)
In this study, we employed a zeolite imidazolate framework (ZIF-67) modified glassy carbon electrode (GCE) as a platform for the electrochemical detection of epinephrine. The ZIF-67 modified glassy carbon electrode (GCE) exhibited excellent electrocatalytic activity towards the detection of epinephrine in phosphate buffer (PBS, pH 7.0). The proposed ZIF-67 displayed superior electrocatalytic activity towards the oxidation of epinephrine in the 0.5−50 μ M linear range with a limit of detection (LOD) of 2.1 μ M, and a sensitivity of 0.06 μ A μ M −1 cm −2 . The efficacy of the proposed biosensor was demonstrated for the direct determination of epinephrine from serum and urine samples. All these results confirmed the usefulness of ZIF-67 modified electrodes for clinical analysis.